Valles vidusskolas vēsture no 1975.gada līdz 2006.gadam - Lapinska, Indra (Latvijas Universitāte, 2006)
Izstrādātā bakalaura darba tēma ir Valles vidusskolas vēsture no 1975.gada līdz 2006.gadam. Bakalaura darba mērķis ir apzināt Valles vidusskolas vēsturi. Uzsākot pētniecisko darbu, tika izvirzīta darba hipotēze - skolas vēstures un attīstības pētniecība paver ceļu izziņai, ka Valles vidusskola ir bijis, un ir joprojām kultūrizglītības centrs pagastā un nodrošina skolas kā organizācijas attīstību. Darba gaitā autore izpētīja Valles vidusskolas vēsturiskos apstākļus, pētīja skolas darbību no tās dibināšanas 1975.gada līdz 1991.gadam, kā arī pētīja un raksturoja skolas darbību no 1991.gada līdz šodienai, pētīja skolēnu un skolotāju darbību. Veiktā bakalaura darba gaitā autore nonākusi pie secinājuma, ka skola ir veikusi un veic savu tiešo uzdevumu – izglītojusi valliešu jauno paaudzi, gatavojusi audzēkņus darba dzīvei, studijām augstākājās mācību iestādēs, audzinājusi cilvēku, kas spējīgs tālāk virzīt dzīves attīstības gaitu.

Topic of the developed Bachelor’s thesis is History of the Valle Secondary School from 1975 to 2006. Purpose of the Bachelor’s thesis is studies in history of the Valle Secondary School. When the research work was commenced, a work hypothesis was posed – research in history and development of the School is clearing the way for knowledge that the Valle Secondary School has been and still is a centre of culture and education for the civil parish and ensures development of the School as an organization. In course of the work historical conditions of the Valle Secondary School were studied, activities of the School from the establishment thereof in 1975 until 1991, as well as activities of the School from 1991 up to date were studied and described, activities of students and teachers were studied by the author. In course of the completed Bachelor’s thesis the author has arrived at a conclusion that the School has performed and is fulfilling the direct task thereof – has educated the rising generation of the population of Valle, has carried out preparations of students for the working life, studies in the higher educational institutions, has trained a human being capable of further advancement to the life development course.
History of Valles Secondary school from 1975 – 2006
Keywords: Pedagoģija